Pancasila Values As Basic Values for Elementary School Students in the National Education System - Saepuddin, Saepuddin (Jurnal Basicedu, 2023)
This research was conducted with the aim of providing an understanding that in the current national education system the values of Pancasila must be instilled as basic values for elementary school students. The reason is that the moral formation of a human being is largely determined from the beginning of his educational development. Therefore, Pancasila values must have existed since elementary school. The method used in this research is library research, namely research on secondary data obtained through library research. The approach is descriptive analysis, namely by collecting data according to the truth, then the data is compiled, processed and analyzed to provide an overview of the existing problem. The results of this research are that in the National Education System, it is clearly stated that education aims to shape students into people of faith, piety and good character. This is in accordance with Pancasila, where Pancasila is a big idea that represents the values in life, because the values of Pancasila are taken from the culture of the Indonesian nation itself, so it is hoped that it can be and can be instilled in everyone from an early age.